Integrating AI chatbots into halal practices: principles, parameters, and guidelines - Mat Jubri@Shamsuddin, Mustafa (Faculty of Law, Governance and International Relations, UNIMEL, 2024)
This study addresses the challenge of integrating AI chatbots into halal practices while adhering to Islamic principles. It aims to identify fundamental Islamic principles governing AI chatbot development, define parameters for their functionality, establish ethical guidelines, and develop a comprehensive framework for their implementation in halal contexts. Employing a qualitative approach through library research, the study analyzes Islamic scholarly texts, academic literature, and contemporary studies on AI in Islamic contexts. The findings reveal that AI chatbots can be considered permissible under Islamic law, subject to conditions aligning with the principles and objectives of Shariah. The study proposes a framework for AI chatbot use in halal domains, emphasizing the importance of accuracy, comprehensive knowledge, user qualifications, and ethical considerations. Guidelines for implementation include ensuring chatbot outputs do not contradict primary Islamic sources, limiting their role to information provision, and maintaining human oversight. The research contributes to the growing discourse on technology in Islamic contexts, offering a structured approach to integrating AI chatbots in halal practices while preserving Islamic values.